2009
DOI: 10.1128/jvi.00632-09
|View full text |Cite
|
Sign up to set email alerts
|

Finger Domain Mutation Affects Enzyme Activity, DNA Replication Efficiency, and Fidelity of an Exonuclease-Deficient DNA Polymerase of Herpes Simplex Virus Type 1

Abstract: The catalytic subunit of herpes simplex virus DNA polymerase (Pol), a member of the B family polymerases, possesses both polymerase and exonuclease activities. We previously demonstrated that a recombinant virus (YD12) containing a double mutation within conserved exonuclease motif III of the Pol was highly mutagenic and rapidly evolved to contain an additional leucine-to-phenylalanine mutation at residue 774 (L774F), which is located within the finger subdomain of the polymerase domain. We further demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The 3=-5= exonuclease and lyase active sites have been mapped within the interior of the 3=-5= exonuclease domain (17,22) and a 63-kDa C-terminal fragment (3), respectively, and are separate from the sites of our engineered mutations within the extreme N-terminal 51 residues at the surface of the enzyme. Additionally, a previous study had reported that a mutant lacking detectable 3=-5= exonuclease activity exhibited a 50-fold decrease in viral yield with only a 3-fold decrease in viral DNA production (40). The defect in viral yield observed in the previous study largely reflected an alteration in replication fidelity rather than a defect in viral DNA synthesis, as seen with our Pol mutants (40).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The 3=-5= exonuclease and lyase active sites have been mapped within the interior of the 3=-5= exonuclease domain (17,22) and a 63-kDa C-terminal fragment (3), respectively, and are separate from the sites of our engineered mutations within the extreme N-terminal 51 residues at the surface of the enzyme. Additionally, a previous study had reported that a mutant lacking detectable 3=-5= exonuclease activity exhibited a 50-fold decrease in viral yield with only a 3-fold decrease in viral DNA production (40). The defect in viral yield observed in the previous study largely reflected an alteration in replication fidelity rather than a defect in viral DNA synthesis, as seen with our Pol mutants (40).…”
Section: Discussionmentioning
confidence: 66%
“…Additionally, a previous study had reported that a mutant lacking detectable 3=-5= exonuclease activity exhibited a 50-fold decrease in viral yield with only a 3-fold decrease in viral DNA production (40). The defect in viral yield observed in the previous study largely reflected an alteration in replication fidelity rather than a defect in viral DNA synthesis, as seen with our Pol mutants (40). Regardless, purification and assay of Pol⌬N52 and PolA 6 proteins relative to WT Pol confirmed that the mutations did not induce any global effects on protein folding, as the mutant proteins exhibited robust 5=-3= polymerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…A HSV-1 polymerase mutant containing Y577H/D581A substitutions was exonuclease-deficient and exhibited a mutator phenotype. However, this variant rapidly evolved a compensatory substitution (L774F) that restored DNA replication fidelity in this genetic background [ 49 , 50 ]. Since RNA virus polymerases typically lack this activity, no such mutators can be produced, except for coronaviruses [ 51 ].…”
Section: Polymerase Fidelity Variantsmentioning
confidence: 99%
“…Conserved polymerase and exonuclease motifs are indicated by colored frames: blue, Exo motifs; green, Pol motifs (Wang et al , 1989); brown, motifs A, B, C (Delarue et al , 1990). Amino-acid substitutions of interest are placed above or below the alignment at the relevant position, highlighted according to the following scheme: aqua, T4 Pol antimutators (Reha-Krantz, 1995a; Reha-Krantz and Wong, 1996; Reha-Krantz, 2010); magenta, HSV1 Pol antimutators (Hall et al , 1984; Gibbs et al , 1988; Hwang et al , 2004; Tian et al , 2009); yellow, yeast pol3-01 ; no highlight, antimutators isolated as suppressors of the pol3-01 mutator phenotype; green, antimutators isolated as suppressors of the pol3-D407A mutator phenotype; orange, antimutators isolated as suppressors of the pol3-F406A mutator phenotype (three substitutions in the same mutant); blue, antimutator isolated as a suppressor of the pol3-D463A mutator phenotype; gray, previously reported antimutators in Pol δ ( pol3-t (D643N), G447S, Y708A, and V758M) (Tran et al , 1999a; Hadjimarcou et al , 2001; Pavlov et al , 2004; Li et al , 2005). The antimutators affecting pol3-01 , pol3-D407A , pol3-F406A , and pol3-D463A are from Herr et al (Herr et al , 2011).…”
Section: Figurementioning
confidence: 99%